New directions for service research: refreshing the process of theorizing to increase contribution. Issue 3 (7th May 2020) - Brodie, Roderick J.; Peters, Linda D.
Abstract : Purpose: For service research to develop as an applied social science there is the need to refresh the process of theorizing so it focuses not only on increasing new academic knowledge but also on knowledge that is managerially relevant. This paper aims to provide guidelines to achieve this. Design/methodology/approach: A theorizing process that integrates general theoretic perspectives and contextual research to develop midrange theory is developed. The process is based on the philosophical foundations of pragmatism and abductive reasoning, which has the origins in the 1950s when the management sciences were being established. Findings: A recent research stream that develops midrange theory about customer and actor engagement is used to illustrate the theorizing process. Practical implications: Practicing managers, customers and other stakeholders in a service system use theory, so there is a need to focus on how theory is used in specific service contexts and how this research leads to academic knowledge that is managerially relevant. Thus, as applied social science, service research needs to explicitly focus on bridging the theory–praxis gap with midrange theory by incorporating a general theoretic perspective and contextual research. Originality/value: The contribution comes from providing a broader framework to guide the theorizing process that integrates general theoretic perspectives and applied research to develop midrange theory. While general theories operate at the most abstract level of conceptualization, midrange theories are context-specific and applied theory (theories-in-use) is embedded in empirical research.